Strangers in a Strange Land: Relations Between Perceptions of Others' Values and Both Civic Engagement and Cultural Estrangement - Sanderson, Rebecca; Prentice, Mike; Wolf, Lukas; Weinstein, Netta; Kasser, Tim; Crompton, Tom (Frontiers in Psychology, 2019)
Healthy democracies require civic engagement (e.g., voting) from their citizens. Past research has suggested that civic engagement is positively associated with self-transcendence values of care and concern for the welfare of others, and negatively associated with self-enhancement values of self-interest, dominance and personal success. However, research has yet to address whether people’s perceptions of others’ values are related to civic engagement. Across three studies with nationally representative samples in the UK and US (Ns ≥ 1,000), we explored how civic engagement relates to a) perceptions of national values, b) perceptions of the values of one’s typical compatriot, and c) perceptions of the values encouraged by social and cultural institutions. Study 1 showed that the tendency for British citizens to perceive British culture as valuing self-transcendence was associated with an increased likelihood of voting in the 2015 general election. These findings were replicated for ‘a typical British person’ (Study 2) and ‘a typical American person’ (Study 3); Studies 2 & 3 also found that perceived self-enhancement values of typical compatriots were negatively correlated with reported voting. We also examined how perceptions of others’ values relate to cultural estrangement—the feeling of not fitting in one’s culture or of being atypical. Like civic engagement, those who perceived less self-transcendence and more self-enhancement in their culture felt more culturally estranged. Mediation analyses in Studies 2 & 3 revealed that estrangement helped to explain the relationship between perceptions of others’ values and voting. In sum, the extent to which Brits and Americans perceive that self-transcendence values are strongly held by other citizens is associated with feeling less estranged and with reports of being more civically engaged. In contrast, the perception that these targets hold or promote self-enhancement values is positively associated with feelings of estrangement, to the detriment of civic engagement. Implications for future research and democratic processes are discussed.